Investigation of Thromboelastography (TEG) - Si, Jonathan E Chen (2016)
Blood coagulation is a process of the human body that is important for recovery from bleeding related injuries. It also extremely important in the operating theatre where patients run the risk of bleeding profusely and other life threatening complications that come with it. There are in fact many tests available today for testing of blood’s coagulation rate and the deficiencies that come from an abnormal coagulation rate. Traditional blood coagulation testing of testing blood with reagents in medical laboratories and later on, point of care devices that test the viscoelastic nature of blood in coagulation are among these tests. Although viscoelastic blood testing has many benefits over traditional testing methods, not much advancement in its technology has occurred since its inception in the 1940s. The objective of this project is to provide a framework and base for a new testing method and to eventually design a prototype capable of running this new method. Behavior of blood within the current viscoelastic test method will be investigated and studied. A similar method of testing blood’s viscoelastic nature was then devised using simple set ups and materials. The testing phase of this project highlights the effects of factors of the environment within the test set up on blood’s viscoelastic properties. The testing phase then provides the pro and cons of several testing methods and draws a conclusion on what works and what does not. This project aims to provide the necessary information on blood coagulation testing and the possibility of a portable and simple blood coagulation testing device. It also contributes a platform for future study and development into this area of research.